2014
DOI: 10.1097/id.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics of Osteotomies Using Different Piezosurgical Devices. A Scanning Electron Microscopic Evaluation

Abstract: The morphological characteristics of the produced Piezosurgical osteotomies vary and depend on the Piezosurgical unit and tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The micrometric cut of ultrasound vibrations permits a precise, controllable cutting action (Rashad et al. ), as also confirmed in morphological evaluation by scanning electron microscope study (Bauer & Romanos ). Piezosurgery technology works selectively on hard and soft tissues (Bovi et al.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The micrometric cut of ultrasound vibrations permits a precise, controllable cutting action (Rashad et al. ), as also confirmed in morphological evaluation by scanning electron microscope study (Bauer & Romanos ). Piezosurgery technology works selectively on hard and soft tissues (Bovi et al.…”
mentioning
confidence: 77%
“…The first clinical report of piezosurgery was published in 2000 (Vercellotti 2000) and provided new possibilities for surgical osteotomies. The micrometric cut of ultrasound vibrations permits a precise, controllable cutting action (Rashad et al 2013), as also confirmed in morphological evaluation by scanning electron microscope study (Bauer & Romanos 2014). Piezosurgery technology works selectively on hard and soft tissues (Bovi et al 2010) and for this reason is frequently used in several bone surgery specialities such as Orthopaedics (Hoign e et al 2011), ENT (Grauvogel et al 2011), Neurosurgery (Follmann et al 2012) and Cranio and Maxillofacial Surgery (Robiony et al 2004).…”
mentioning
confidence: 92%
“…Piezosurgery is recommended in complicated impacted teeth extractions nowadays45. Compared with chisel and drill, the piezosurgry effects mainly on the mineralized tissues, thus the borders of the area affected can be determined accurately11.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the chisel and drill, the piezosurgery is the best to be introduced in complicated wisdom tooth surgery with higher accuracy and safety456. Tooth sectioning could also help release adjacent tooth resistance7.…”
mentioning
confidence: 99%
“…10 The osteotomy is performed by means of pendular vibratory movements, with nanometric variations of amplitude, by the use of various points. 11 Nowadays, international consensus or scientific literature about the possibility to perform oral rehabilitation and maxillary sinus grafting in the case of pre-existing sinus membrane pathology are not present. Bone density and local inflammatory processes influence the operative protocol and the choice of the type of implant used in order to replace the lost teeth 12 and maxillary bone losses often require additional surgical procedures.…”
Section: Introductionmentioning
confidence: 99%